Low-temperature synthesis of nanocrystalline powders of lithium ferrite by an autocombustion method using citric acid and glycine - Verma, S.; Karande, J.; Patidar, A.; Joy, Pattayil Alias (Materials Letters, 2005)
Nanocrystalline lithium ferrite is synthesized by an autocombustion method from the corresponding metal nitrates using citric acid as well as glycine as fuels. The ordered phase of lithium ferrite, in single phase form, with particle size of 32-36 nm and large coercivity, is obtained by this method at a low temperature of 200 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Combustion synthesis; LiFe5O8; lithium ferrite; low-temperature synthesis; Magnetic materials; Nanomaterials

Magnetic properties of nanosized ferrite powders synthesized by microwave-hydrothermal method - Khollam, Y. B.; Dhage, S. R.; Verma, S.; Potdar, H. S.; Deshpande, S. B.; Joy, Pattayil Alias; Date, Sadgopal K. (Ninth International Conference on Ferrites (ICF-9), 2005)
Nanosized powders of Fe3O4 and MgFe2O4 are synthesized by microwave-hydrothermal (MH) method. The ferrite powders thus obtained are characterized by powder X-ray diffraction, Mossbauer spectroscopy, scanning and transmission electron microscopies, vibrating sample magnetometer and AC magnetic susceptibility studies. Stoichiometric, nanosized (similar to 34 nm) Fe3O4 particles, having cubic symmetry with a(0) approximate to 8.39 angstrom, are obtained when molar ratio of Fe/NaOH used for the synthesis is 0.133. On the other hand, non-stoichiometric Fe3O4 is obtained when Fe/NaOH molar ratio is increased to 0.4. Though the powder XRD patterns of both stoichiometric and non-stoichiometric Fe3O4 are identical, Mossbauer spectroscopic studies showed different features in terms of asymmetry, intensity, isomer shift, etc. Saturation magnetization, M-s = 70 emu/g and coercivity, H-c = 178 Oe, at room temperature, are obtained for stoichiometric Fe3O4 powders. In the case of MgFe2O4, spherical, nanosized (similar to 3 nm) powders with cubic symmetry (a(0) approximate to 8.30 angstrom) and having very narrow size distribution are obtained under the MH conditions. The temperature and field dependent magnetic measurements on MgFe2O4 powders confirmed the existence of superparamagnetic state in this material with a superparamagnetic blocking temperature of 38 K below which typical magnetic hysteresis behaviour is observed.

Novel low-temperature synthesis of nanosized NiZn ferrite - Verma, S.; Pradhan, S. D.; Pasricha, R.; Sainkar, S. R.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2005)
Nanosized NiZn ferrite powder is synthesized by a low-temperature method, using a unique combination of citric acid and glycine. An appropriate molar ratio of both citric acid and glycine offers a low-temperature synthetic route by incorporating the complexation behavior of citric acid and the combustion nature of glycine. Thermal decomposition/controlled autocatalytic combustion of the composite gel occurs at a low temperature of around 175 degrees C, with the evolution of a large amount of gases. Transmission electron microscopic studies showed that the average particle size of the ferrite obtained is similar to 2.5 nm, with a narrow size distribution. Uniformly distributed fine-grained microstructure with low porosity is obtained for a sample sintered at 1000 degrees C.